Peningkatan Kemampuan Membaca Puisi Dengan Menggunakan Media Audio Visual Pada Siswa Kelas III SD Negeri - Saputra, Septia Irnanda (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research is motivated by the teacher is use of media-based technology, and student’s   mastery learning standards in science learning. The purpose of this study was to describe the potentiality reading poetry using audio-visual media for students of class III. This research is a classroom action research (CAR). The approach used is a qualitative and quantitative approach. Thus, audio visual media can approach the potentiality reading poetry class III students. Kata Kunci : kemampuan membaca puisi, media audio visual, sekolah dasar